2011
DOI: 10.1111/j.1749-4486.2011.02297.x
|View full text |Cite
|
Sign up to set email alerts
|

Do wind and brass players snore less? A cross‐sectional study of snoring and daytime fatigue in professional orchestral musicians

Abstract: This study demonstrated no significant difference between the snoring severity or daytime sleepiness of brass/wind players and other professional orchestral musicians. This result may have been attributed to comparatively low levels of snoring/daytime sleepiness in the population studied. The findings contrast with previous studies examining the effects of singing and didgeridoo playing but concur with a recent similar study of orchestral musicians. A prospective interventional study would be required to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Wardrop et al [15] demonstrated no significant difference between the snoring severity or daytime sleepiness of brass ⁄ wind players and other professional orchestral musicians although in a questionnaire-based observational study. While the properties and structure of the pharyngeal muscles are different in severe OSA patients compared with snorers and controls [16] the extent to which these changes are acquired or inherited and their function role in OSA pathogenesis are unclear.…”
Section: Discussionmentioning
confidence: 90%
“…Wardrop et al [15] demonstrated no significant difference between the snoring severity or daytime sleepiness of brass ⁄ wind players and other professional orchestral musicians although in a questionnaire-based observational study. While the properties and structure of the pharyngeal muscles are different in severe OSA patients compared with snorers and controls [16] the extent to which these changes are acquired or inherited and their function role in OSA pathogenesis are unclear.…”
Section: Discussionmentioning
confidence: 90%
“…Data extracted from the included studies are presented in Table 3, which provides a summary overview of sleep/snoring/ OSA parameters between wind instrument players/singers and a control group. According to the results of 3 of the included studies, 40,41,44 there seems generally to be no difference in sleep, snoring, and OSA between wind instrument players and controls. Two exceptions are double-reed instrument players, The search strategy was customized according to the database being searched.…”
Section: Descriptive Analysismentioning
confidence: 96%
“…Thus, in total, 6 papers (Figure 2) were included in the present systematic review. [39][40][41][42][43][44]…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations